Do species of Crataegus sect. Sanguineae occur in Iran?. (12th May 2015) - Hamzeh'ee, Behnam; Attar, Farideh; Zieliński, Jerzy; Assareh, Mohammad Hasan; Mozaffarian, Valliolah
<x xml:space="preserve">Abstract</x> Results of a revision of Iranian species of Crataegus section Sanguineae are presented here. Previously, two species of this section, C. sanguinea Pall. and C. babakhanloui Khat., were reported from Iran. However, detailed analyses of morphological and micro‐morphological characteristics, as well as phytogeographical data, could not confirm this information; herbarium specimens recognised as C. sanguinea appeared to be C. pentagyna Waldst. & Kit. (C. sect. Pentagynae), while C. babakhanloui should be included in the C. section Crataegus. The section Sanguineae is represented in Iran only by C. wattiana Hemsl. & Lace, the presence of which is reported here for the first time.